To write the explicit rule, we need some information about the following series:

3, 6, 12, 24, 48, ...

In Blank 1: a1 =
In Blank 2: r =

Respuesta :

Answer:

see explanation

Step-by-step explanation:

Note the common ratio r between consecutive terms of the sequence

r = 6 ÷ 3 = 12 ÷ 6 = 24 ÷ 12 = 48 ÷ 24 = 2

The explicit rule for a geometric sequence is

[tex]a_{n}[/tex] = a₁[tex](r)^{n-1}[/tex]

where a₁ is the first term and r the common ratio

Here a₁ = 3 and r = 2, thus

[tex]a_{n}[/tex] = 3[tex](2)^{n-1}[/tex] ← explicit rule